Genetic Identification of Symbiotic Algae (Symbiodiniaceae) in Coral Bleaching on Sambangan Island, Karimunjawa - Vina Zubaida; Dwi Haryanti; Munasik Munasik; Diah Permata Wijayanti; Tanya Singh (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Recently, there has been a global decline of coral reef ecosystems, primarily caused by major threats such as global warming. This phenomenon has a significant negative impact on coral reefs, including rising sea temperatures that trigger of coral bleaching. Composition of symbiotic algae, Symbiodiniaceae, in corals determines how corals respond to environmental stress.  This study aimed to investigate the community of the symbiotic algae during bleaching event by applying molecular identification technique. Coral bleaching samples from different genera were randomly collected from three different location around Sambangan Island, Karimunjawa at the depth of 1 – 2 m. DNA Barcoding of Internal Transcribed Spacer (ITS1, 5.8 rRNA and ITS2) gene were performed. Our result shows that four types of Symbiodiniaceae were closely related to the symbiotic algae found in this study, i.e. Cladocopium goreaui, Cladocopium sp., Symbiodinium sp. Clade C, and Symbiodinium sp. C1. The phylogenetic tree analysis showed that all the Symbiodiniaceae species found formed a single clade with a low genetic distance value. All of these species belong to the same genus Cladocopium. This type of symbiotic algae is known to have broad tolerance to temperature changes and other stress factors.